Market chain analysis of chickpea in Northwest Ethiopia - Chernet Worku; Mulat Mengistu; Sosina Bezie (Legume Science, 2023)
Abstract The purpose of the paper is to explain the organization, behaviours and output of smallholder farmers of chickpea market and to analyse the structure–conduct–performance (S‐C‐P) of chickpea in the study area. The study was supported by a recent empirical study and used primary and secondary data from 122 respondents, as well as published and unpublished documents, to better understand how market structure and seller behaviour affect market performance. The study was conducted using the S‐C‐P model analytical approach. Weak oligopoly dominates the chickpea market in the research area (concentrated in the hands of few traders). The goal of the study was to fill the knowledge gap that existed on the topic, contribute to a proper understanding of the difficulties and enhance market development strategies for the benefit of producers, traders and other market participants. According to the research of the market structure, the district market has an oligopolistic market structure with a concentration ratio of 43.35%. In addition, the market is restricted by entry‐level obstacles such as a lack of funding, licensing requirements, the issue of constant supply and a lack of prior expertise in chickpea trading activities. The oligopolistic market structure has also led to chickpea market behaviours that is distinguished by a market strategy where the traders have the upper hand in determining the chickpea price. The study focuses on raising farmers' educational levels, enhancing extension and finance services, building transportation facilities to provide producers more negotiating leverage and accessing improved production techniques as a way to choose the best marketing outlet. Government agencies and relevant parties must step in to address the issues by disseminating current market data on the chickpea industry, enhancing market connectivity and supplying the market with their goods at competitive prices.